The Impact of Flexible Work and Social Support on Employees' Work-Life Balance - Tamin Tamin; Agus Halim (Advances in Management & Financial Reporting, 2026)
Purpose: This study seeks to understand how work flexibility and social support can help employees effectively balance professional demands and personal life. Research Method: This study uses a descriptive quantitative approach. Data collection techniques include observation, interviews, documentation, and distribution of questionnaires to all employees. Data analysis is performed using multiple linear regression to test relationships among variables, with partial (t-tests) and simultaneous (F-tests) tests used for hypothesis testing. Results and Discussion: The results show that Flexible Work and Social Support have a positive and significant effect on Work-Life Balance, both partially and simultaneously. This confirms that work flexibility and adequate social support can reduce work stress, improve emotional well-being, and strengthen employees' attachment to the organization. Implications: This study emphasizes the importance of implementing flexible work policies and a supportive work culture as human resource management strategies to improve job satisfaction and organizational sustainability.